Targeting smart shoppers: a cross-country model - Gómez-Suárez, Mónica; Quinones, Myriam; Yagüe, María Jesús (Journal of Business Economics and Management, 2020)
The purpose of this article is to provide a robust and consistent cross-country measurement of the smart-shopper self-concept. Drawing on existing single-country studies, our work extends research by validating a pioneer cross-country scale that measures the smart-shopping mechanism in a holistic manner. Survey data were collected from 1,233 shoppers from six different Western countries. Cross-country equivalence was assessed using multigroup confirmatory factor analysis using configural, metric, and factor variance invariance tests. The results indicate that the smart-shopper self-concept is a second-order construct comprising two dimensions: smartshopper-attributed behavior and smart-shopper feelings. Our findings also reveal that consumers in the different countries exhibit different degrees of smart-shopper self-concept and differ in their perceptions of the affective and behavioral responses generated during a smart purchase process. Marketing practitioners looking to target smart shoppers across multiple countries could build on the findings of this study to develop effective international segmentation and positioning strategies.